Vocabulary of crime against heritage - Meza Lagos, Consuelo (2016)
Criminals have multiplied the theft patterns in many areas of our Peruvian society. The first to reflect such situation is our lexicon, which gives a significant increase in recent times. The contribution of these new voices does not only come from the criminal world, but also from the forces of order, who to identify each modality have turned to the creation of a very varied lexicon, both to identify the type of robbery and the offender who executes it. In some cases, one voice has been replaced by another since it is considered more accurate; in other cases the list has been increased to specify the crime. In the present article, we introduce the lexicon of the different types of crime against heritage; distributed in semantic areas such as the banking system (credit card subfields, ATMs), house burglaries (sub-mode of entry to the house with Fracture or without door breaking), vehicle theft, pedestrian theft (subfield with or without weapons) and robberies to shopping centers.